Professional capabilities needed in the process of equipping the army with armament and military equipment - Brkljač, Nenko S.; Andrejić, Marko D.; Ilić, Slobodan S. (Vojnotehnički glasnik / Military Technical Courier, 2014)
This paper presents the results of the research into necessary capabilities (knowledge and skills) in the process of equipping the army. The necessary professional capabilities have been analyzed from the viewpoint of protecting the interests of customers and end-users of armament and military equipment.The capabilities are grouped according to the key activities of the process and analyzed through the following activities: planning and programming, defining tactical and technical requirements, contract making, research, development, testing, production, procurement, operational use, support and end of service life of armament and military equipment. The capabilities have been described in two ways, through a detailed description of a necessary capability, or through a description of the effect required from qualified personnel engaged in the process of equipping the army.
Keywords: quality; process; capability; knowledge; requirements; quality of service for armaments